Reliability and Validaty of St George Respiratory Questionnaire (SGRQ) into Indonesian Version - Adnan Adnan; Dyah Aryani Perwitasari; Ully Adhie Mulyani (International Journal of Public Health Science (IJPHS), 2014)
Tuberculosis (TB) is one of the disease as the highest contributor to the disease burden in Indonesia. Tuberculosis can affect the patients’ quality of life, such as psychological, physical, and social functioning. St. George's Respiratory Questionnaire (SGRQ) is a special instrument which was widely used to measure the patients’ quality of life with respiratory disease. The objective of this study was to validate the Indonesian version of the SGRQ as instrument to collect data. A descriptive cross section design with 61 subjects was conducted at the Pulmonary Clinics and Primary Health Centers in the region of Yogyakarta within 3 months. The validation process included the known group validity, convergent and discriminant validity and factor analysis. There were 14 items question numbers which did not meet the criteria for convergent validity and 9 items which did not meet the criteria for discriminant validity. Known group validity analysis on gender showed that of the three domains of SGRQ, the activity domain gave statistically significant result. The factor analysis showed the result of Kaiser Meyer Olkin analysis (KMO) was less than 0.5. With a few modifications, the Indonesian version of SGRQ is valid and reliable for measuring quality of life in tuberculosis patients.